The impact of macroeconomic factors and internal company variables on the profit of textile and garment sector companies listed on the indonesian stock exchange - Winarto, Jacinta; Susan, Marcellia; Hartawati, Hartawati (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The COVID-19 pandemic has profoundly influenced various sectors, including monetary, social, economic, and humanitarian aspects. Economically, one prominent consequence was the turmoil in global financial markets at the start of 2020, which prompted a shift in global asset allocations and caused currency depreciation in emerging markets such as Indonesia. The textile industry was also impacted due to disruptions in the supply chain for raw materials, leading to higher product costs and, consequently, inflation. Additionally, the implementation of work-from-home policies during this period led to reduced exports and domestic sales, resulting in liquidity challenges and difficulties in debt repayment within the textile sector. These circumstances suggest that exchange rates, inflation, debt, and liquidity were likely contributing factors to the decline in profitability. Profitability need to be considered as they can impact the sustainability of the company. This study aims to examine and evaluate the influence of inflation, exchange rates, debt, and liquidity on corporate profitability. The research focused on textile companies listed on the Indonesia Stock Exchange during 2021–2022, with samples chosen through purposive sampling method. The purposive sample is conducted based on companies that publish complete financial statements during the study period and are not outliers. The selected sample consists of 14 companies. Panel data regression analysis was employed to process the data. Panel data regression analysis is chosen to identify the relationship between macroeconomic factors, internal company variables, and company profitability. The results revealed that inflation, exchange rates, and liquidity had no significant effect on company profits, while debt had a negative impact. The coefficient for each variable's effect on profits are as follows: exchange rate is 0.00001, inflation is -1.0285, debt is -0.0996, and liquidity is -0.0001. Based on these findings, it is suggested that companies improve debt management by negotiating payment terms with suppliers to minimize reliance on bank credit and optimize profitability.